Hospitalization experience and associated factors among Chinese patients with cancer: a cross-sectional study - Wenjuan Gao; Youyou Hu; Huayi Chu; Doudou Yu; Keyi Tang; Xiuwen Chen; Ying Zhu; Jing Han (BMC Nursing)
Abstract Background Although hospitalization experience is recognized as critical to patient well-being and nursing quality, its role within Chinese healthcare system remains understudied, particularly among cancer patients. This study aims to capture the associated factors of Chinese cancer patients’ hospitalization experience, with the goal of informing targeted improvements in care delivery. Methods A convenience sampling method was employed to survey 351 cancer inpatients from three tertiary hospitals in China from September to November 2024. Data were collected using the Patient-reported Experience Measure for Cancer (PREM-C), the Hospital Service Quality Questionnaire (HSQQ), and the Family APGAR Index (APGAR). The acquired data were analyzed using the Shapiro-Wilk test, univariate analysis, and multiple linear regression. Results The mean scores for PREM-C, HSQQ, and APGAR were 92.47 ± 8.62, 82.22 ± 8.05, and 8.26 ± 1.45, respectively. Multiple linear regression analysis indicated four factors associated with cancer patients’ overall hospitalization experience, including payment of medical costs (β = −0.170, p < 0.001), type of cancer (β = 0.128, p = 0.026), quality of hospital services (β = 0.367, p < 0.001), and family function (β = 0.163, p = 0.001). Conclusion Patients with higher-quality hospital services, stronger family functioning, or medical insurance report more positive hospitalization experiences. Gynecological cancer patients also report better experiences than those with other cancer types. This study highlights hospital service quality and family functioning as key influences on cancer patients’ hospitalization experience, advocating tailored support for different cancer types. Clinical trial number Not applicable.